Quit Lit”? The Rising Star of ELT, the Declining Fortunes of English Studies and the “Crisis” in Humanities in Sri Lanka - Wickramagamage, S. (Faculty of Arts University of Jaffna, Sri Lanka, 2022)
This paper draws attention to a “crisis” that may, at one level, be generalized under the broader crisis in the Humanities but could, at another level, be unique to English Studies in Sri Lanka. I refer to the “fall” of “English” and the corresponding rise in ESL or ELT degrees at state universities in Sri Lanka. I discuss how this displacement of the one and its gradual replacement by the other would have been unthinkable a century ago when the idea of a Ceylonese University was first mooted and the University of Ceylon was established. I will highlight the complex constellation of factors, from post-independence national policies relating to English and English language teaching, the emergence of English as a global language, and funding priorities of international (World Bank) donor agencies to improve the “employability” of graduates to shifts in perceptions vis-à-vis English as well as perceivable trends in English language competencies among the youth, that have brought about this situation and how current course offerings in both state and private universities in Sri Lanka reflect these new demands. The paper asks what this means specifically for English Studies as it was traditionally conceived and practiced in Sri Lanka, and for Humanities education in general. Would it finally convert the kaduva [=sword] into an hända [=ladle], thus ensuring more equitable access to English, one that is, at long last, regarded in purely instrumental terms? Is English Studies in Sri Lanka necessarily elitist and neocolonial in orientation? Pedagogically speaking, is literature, which is a key component in a holistic Humanities education, necessarily expendable in the ELT classroom?
Keywords: English studies; English language teaching; Democratizing english; Literature in ELT classrooms